SYNTHESIS, IN VITRO ANTIOXIDANT AND ANTIMICROBIAL EVALUATION OF 3-HYDROXY CHROMONE DERIVATIVES - Kamble, Pallavi; Wadher, Sailesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the present study was to synthesize a series of 3-hydroxychromone derivatives and to evaluate its in vitro antioxidant and antimicrobial activities. Methods: 3-hydroxy chromones were synthesized using an algar flynn oyamada method which includes oxidative cyclization of 2-hydroxy chalcones in basic solution by hydrogen peroxide. 2-hydroxy chalcones were synthesized by Claisen-Schmidt condensation of substituted 2-hydroxy acetophenones with substituted aromatic aldehydes using polyethylene glycol-400 as a recyclable solvent. The synthesized compounds were evaluated for in vitro antioxidant activity by 1,1-diphenyl-2-picrylhydrazyl radical scavenging assay. In addition, these compounds were also screened for in vitro antibacterial and antifungal activity by agar cup method and Poison plate method, respectively. Results: The structures of the synthesized compounds were characterized by infrared, 1H nuclear magnetic resonance and mass spectroscopy. The antioxidant activity data revealed that all the synthesized derivatives exhibited good activity due to the presence of phenolic hydroxyl group, 4-oxo group and 2,3-double bond. Further, the activity increased with the introduction of a more phenolic hydroxyl group and adjacent methoxy group in the structure. The antimicrobial activity data showed that the compounds possess better antibacterial and antifungal activity which is attributed to the presence of phenolic hydroxyl group and 4-oxo group in the structure. Conclusions: The use of inexpensive, eco-friendly and readily available reagents, easy work-up and high purity of products makes the procedure a convenient and robust method for the synthesis of title compounds. The presence of phenolic hydroxyl group, 4-oxo group, and 2,3-double bond in the structure is responsible for their good antioxidant and antimicrobial activities.